MICROBIAL SOIL RESPIRATION AND IT’S DEPENDENCY ON SOIL MICROBIAL COMMUNITIES, ORGANIC CARBON & MOISTURE IN DIFFERENT DRY TROPICAL ECOSYSTEMS - MONTY KUJUR; AMIYA KUMAR PATEL (International Journal of Pharma and Bio Sciences, 2014)
The relationship between environmental changes and microbial respiration is critical for projecting changes in soil carbon fluxes. The variation in OC, microbial-C and moisture among different soil profiles of Jharkhand, India were analyzed. The OC, microbial-C and moisture varied from (0.174-2.469)%, (55.586–646.703) mg/g soil and (6.643–11.329)% respectively. The OC was positively correlated with microbial-C (r=0.985; p<0.01) and moisture (r=0.979; p<0.01). The MB-C:OC ratio ranged from (2.6-3.9) %, and BSR:OC from (1.271-0.382)%. The basal soil respiration and microbial metabolic quotients ranged from (0.348-0.945) mg CO2-C/g soil/hr and (6.2605-1.4612)x10-3 mg CO2-C/g microbial-C/hr respectively. Microbial populations across the sites were estimated. Stepwise multiple regression analysis determines the degree of influence contributed by microbial community, OC, microbial-C and moisture on microbial soil respiration. Principal component analysis was able to discriminate different soil profiles, which correlated well with land degradation, and thus can serve as a biomarker of soil fertility.